Preparation of Specific Antiserum of Secretin and Its Use in Time-Resolved Fluoroimmunoassay - MAEDA, Masako; KODAMA, Ryoko; ITO, Katsutoshi; TSUJI, Akio (YAKUGAKU ZASSHI, 1995)
We have prepared a specific anti-secretin antiserum and developed a sensitive time-resolved fluoroimmunoassay (TR-FIA) for secretin. An anti-secretin antiserum was produced in rabbit by immunization with synthetic secretin C-terminal 8 residue conjugate to chicken serum albumin as antigen. The TR-FIA was based on the competition between free secretin and biotinylated secretin as a tracer for rabbit anti-secretin antibodies on a goat anti-rabbit IgG antibody coated microtiter plate. After separation of bound and free fractions, a solution of europium (III) ion chelate labeled streptavidin (Eu-SA) was added to the biotinylated secretin bound on the microtiter plate. The microtiter plate was washed and then Eu-SA activity was measured by time-resolved fluorometry. In this TR-FIA, the measurable range of secretin was from 2.5 to 100pg/assay and the specificity was less than 0.01% against other peptide hormones. For the measurement of secretin in the human plasma, a sample was required for the pretreatment in order to separate from interfering substances. The mean recovery of secretin using commercially reversed phase column was 80.2% (n=11). The plasma secretin concentrations of normal subjects and those with various diseases could be measured by this proposed TR-FIA.